Discrimination in the rental housing market: a field experiment in Ireland. Issue 3 (17th February 2022) - Gusciute, Egle; Mühlau, Peter; Layte, Richard
ABSTRACT: This paper presents the results of a first field experiment on ethnic discrimination in the rental housing market in Ireland. In addition, it is one of the few studies, in the European context, to consider ethnic discrimination against European and non-European migrants. The experimental design involved creating six fictitious applicants with different ethnic and gender names. These applicants applied for vacant rental apartments advertised online. Results of the experiment show that Irish applicants are more likely to be invited to view an apartment than both Polish and Nigerian applicants. In addition, Polish applicants are more likely to be invited to view an apartment than Nigerian applicants, which points to discrimination between minority groups. There is also evidence of gender discrimination with females receiving more invitations to view apartments than male applicants. Overall, the Irish female is the most likely to receive an invitation to view an apartment and the Nigerian male is the least likely, with a statistically significant lower response rate of 23 per cent.